STRATEGI PEMASARAN RUMAH BERSUBSIDI PADA PT ANUGRAH INDAH BERSAMA LAMPUNG - Oktaviani, Ayu; Yusa, Viola De; Utami, Riyadini Riyan (Lembaga Pengembangan Kinerja Dosen, 2023)
Abstract Housing is one of the basic human needs, not individual needs but the needs of society as a whole. However, not all people can enjoy or have decent, healthy and safe housing, so efforts to increase housing and settlement development must continue to be increased at affordable prices, especially for low-income groups. One of the causes of the problems faced by big cities in Indonesia is the large population caused by natural growth and urbanization. The government program through the construction of subsidized housing targets low-income communities (MBR). The purpose of this research is to determine the choice of marketing strategy through SWOT analysis as an effort to increase subsidized housing sales at PT Anugrah Indah Bersama Lampung in the pandemic era. The type of research used is descriptive qualitative, namely research conducted to determine the value of independent variables, which interpret data in the form of words, sentences, schemes and pictures through SWOT analysis. Based on the several stages of analysis that have been carried out on IFAS and EFAS analysis, the strength of PT. Anugrah Indah with Lampung is superior to its weaknesses. The opportunities from PT. Anugrah Indah and Lampung are involved in a large enough threat compared to the threat.